PENGARUH PROFIT MARGIN, INVESTMENT TURNOVER, EQUITY MULTIPLIER TERHADAP RETURN ON EQUITY - Animah Animah; Elin Erlina Sasanti; Nina Karina (Program Magister Akuntansi Unsyiah, 2009)
The title of this research is The Influence of Profit Margin, Investment Turnover, Equity Multiplier toward the Return on Equity of Bank Pembangunan Daerah (BPD) in all over of Indonesia from the year of 2002 to 2006. The objectives of this research are 1) Is there any significant influence among profit margin, investment turnover, and equity multiplier simultaneously toward the return on equity at BPD all over Indonesia in the range of year of 2002-2006. 2) Is there any significant influence among profit margin, investment turnover, and equity multiplier partially toward the return on equity at BPD all over Indonesia in the range of year of 2002 to 2006.The sampling technique used in this research was purposive sampling with judgment and the sampling obtained by using this technique were 16 BPDs. The data analysis method used in this research was the multiple linear regressions.The analysis results showed that there were significant influence simultaneously (89,6%) and partially (less than 0.05%) for all the variables toward the return on equity.Keyword : Profit Margin, Investment Turnover, Equity Multiplier and Return on Equity